EFFECT OF SILVER THIOSULPHATE, SILVER NITRATE AND DISTILLED WATER ON FLOWER QUALITY AND VASE LIFE OF CUT CARNATION FLOWERS - RUPALI SHARMA,; ANDEEP BHARDWAJ, (The Bioscan, 2015)
The present investigation was undertaken during the years 2006-07 and 2007-08 at Model Floriculture Centre, Govind Ballabh Pant University of Agriculture and Technology, Pantnagar (Uttarakhand) with carnation genotypes. 16 carnation genotypes were planted in completely randomized block design under low cost polyhouse. These genotypes were also selected for post harvest analysis by using completely randomized block design with treatments as factorial combination of 16 cultivars and 3 levels of different holding solutions (STS, AgNo 3 and distilled water). Ferada and Sunrise in distilled water had highest value of days taken to bud opening (5.12 days) whereas Keyar in STS solution (2.63 days) was recorded with minimum value. Flower diameter was found to be maximum (6.41 cm.) with Liberty which exhibited significantly higher diameter than all the genotypes in different holding solutions, while minimum (2.94 cm.) was recorded with Salaya which was at par with Dubesco Rubesco (3.11 cm.). Minimum Percent of flower weight loss was found with Ferato (13.26%) in STS solution which was at par with Tabour, Dark Randevous, Master, Ferada, Liberty, Tabour while maximum percent of weight loss was recorded in Parado Fansi (47.19%) which was at par with Sunrise (44.43%) in distilled water. Maximum amount of solution uptake was recorded with Tabour (36.56 ml) when kept in solution and minimum (11.07 ml) amount of solution was consumed by Sunrise when kept in distilled water. Maximum Vase life was recorded with Ferato(13.90 days) in STS solution which was at par with Tabour (13.64 days) while minimum (5.88 days) vase life was recorded with Cv. Lavender lace in distilled water, which was significantly lesser than all the genotypes in different holding solutions.